EVALUATION OF EFFECT OF EUGENOL PLANT ONTWO OF CANCEROUS CELLULAR LINES (AMN3) ANDNORMAL (REF) - Al-Thwani, Amina; Nseaf, Sanar (Iraqi Journal of Science, 2024)
The capacity of aqueous and alcoholic extract of Dianthus was studied on twocell lines, which were: many adino carcinoma (AMN3) and normal cell line of Ratembryo fibroblast (REF) in vitro and the effect was evaluated of these extractsIt was found that the crude extract of Dinthus contained resins, saponins,flavonoides, comarins and phenols. Aqueous and alcoholic extract of Dianthusshowed a high inhibition activity on cancer cell lines in all concentrations used andthe effects of Dianthus appeared after 48 hours. From being exposed on the cell inconcentration of 1000 mg/ml.The highest inhibition result in AMN3 cells were 58.3, 66.7% for both extractsaqueous and alcoholic and the inhibition effects were similar in both cell line and thebio results of these cells explained the inhibition effects for the biology of cellsdepend on the concentration of crude extract and type of solvent being used.